Efektivitas Penggunaan Game Kahoot terhadap Hasil Belajar Siswa Mata Pelajaran PAI XI SMAN 1 Lembang Jaya - Wahyuni, Sofia Putri; Alfurqan, Alfurqan (ALSYS, 2023)
This research is motivated by the current learning atmosphere which has not been able to motivate students well, resulting in student learning outcomes that are not yet optimal. This is because the exercises in the learning process are still not varied enough, one example of training that can be used is Kahoot. This research aims to determine the effectiveness of using the Kahoot quiz game on the learning outcomes of class IX students at SMA Negeri 1 Lembang Jaya. This research uses a quantitative approach with the experimental method "post test only control group design". The population in this study were all class IX students of SMA Negeri 1 Lembang Jaya. The research sample consisted of 23 students of class XI IPS as the experimental class and 23 students of class The test results were compared using the t-test formula to determine the effectiveness of using the Kahoot quiz game. Based on the t-test results, it was concluded that learning using Kahoot was significantly effective for PAI learning for class XI students at SMA Negeri 1 Lembang Jaya. The results of effectiveness testing using an effect size of 1.814 show that the effect of using the Kahoot online game is high (d=1.814>0.8). This indicates that the use of Kahoot has a significant positive impact on improving student learning outcomes in class XI PAI subjects at SMA Negeri 1 Lembang Jaya.